Changing policies changing times: Teacher Education in England (or throwing the baby out with the bathwater) - Hilton, Gillian (Acta Paedagogica Vilnensia, 2012)
For many years now, in England the ways to train for the profession of teaching have been varied, but most teachers have been prepared through the Postgraduate Certificate in Education Course. The majority of this course takes place in school (two thirds of the time for secondary trainees, rather less for primary). In their time in university, students are given grounding in education theory, teaching and learning, classroom control and other essential aspects such as teacher professionalism. Much of this is completed with the support of partner schools where trained mentors supervise the practical application of theory. Now, proposals by the Secretary of State for Education are attempting to virtually remove teacher education from universities by giving it into the control of schools, based on the belief that teaching is merely a ‘craft’ and not an academic discipline. The resistance to this idea from the majority of the profession is huge, but will the practitioners be heard?